ANALYSIS OF SINGLE-VEHICLE AND MULTIPLE-VEHICLE CRASHES ALONG THE HAWAN KIBO CRASH CORRIDOR, PLATEAU STATE, NIGERIA - Bombom, L. S.; Jambol, Antele R.; Bot, Emmanuel T.; Ibimode, Akinwumi A.; Dabis, Nandi D. (FUDMA JOURNAL OF SCIENCES, 2023)
In-depth analysis of the characteristics of road traffic crashes at blackspots or hotspot locations is, generally, insufficient in Nigeria. This is despite the fact that blackspots represent recognized locations with road safety deficiencies and mitigation of crashes at such locations produce multiple benefits. This paper examines characteristics of road traffic crashes along Hawan Kibo route, one of the most recognized crash corridors in Nigeria, with particular emphasis on single-vehicle (SV) and multiple-vehicle (MV) crashes. The data shows that between 2015 and 2019, 355 crashes were recorded (SV: 219; MV: 136), with 1288 persons sustaining injuries (SV: 652; MV: 636) and 121 fatalities (SV: 46; MV: 75). The most important causes of crashes and casualties for SV crashes were brake failure, speed violation, and fatigue; while wrongful overtaking, brake failure and speed violations were the most prominent for MV crashes. Time of day for crashes was not significantly different between SV and MV crashes but number of persons injured per crash was significantly different between them. Though MV crashes were less in number, they appeared to be more severe. There was no statistically significant difference between the fatality rates per crash for SV and MV crashes even though SV fatality rates were significantly less than those for MV crashes. In the light of the fact that the most prominent causes of crashes and casualties are associated with poor human judgment and attitude, the study suggests that more creative and concerted efforts should be made to educate drivers and passengers on road...